Impact of continuous positive airway pressure in patients with obstructive sleep apnea during drug‐induced sleep endoscopy. (21st March 2017) - Torre, C.; Liu, S.Y.; Kushida, C.A.; Nekhendzy, V.; Huon, L.K.; Capasso, R.
Abstract : Objectives: The primary objective of the study was to understand the differential impact of continuous positive airway pressure (CPAP) on the location, degree and pattern of airway collapse in obstructive sleep apnea (OSA) patients utilizing drug‐induced sleep endoscopy (DISE). Study design: Non‐randomized trial. Setting: University Medical Center. Participants: Fifteen consecutive OSA patients undergoing DISE. Main outcomes and measures: The patterns of airway collapse were videorecorded at baseline and under differential application of nasal CPAP (nCPAP) at 5, 10 and 15 cm H2 O. For each modality, the pattern and degree of airway collapse were analyzed by three independent observers using the velum, oropharynx, tongue base, epiglottis (VOTE) classification system. Results: The modest nCPAP pressures (10 cm H2 O) had the greatest impact on the lateral walls of the pharynx, followed by the palatal region. The collapsibility of the tongue base and epiglottis demonstrated significant resistance to nCPAP application, which was overcome by increasing nCPAP to 15 cm H2 O. Compared to 5 cm H2 O, nCPAP pressures of 10 and 15 cm H2 O improved complete collapse at least at one level of the upper airway ( P =.016 and .001, respectively). Increased nCPAP pressures also led to changes in the configuration of airway collapse at the level of the velum. Conclusions: The differential nCPAP effects observed in this study may help to understand some of the mechanisms responsible for inadequate patient response and poor nCPAP compliance. The use of DISE in combination with CPAP may serve as a first step in optimizing patients that failed to adapt to treatment with CPAP. This approach can help the physician identify patterns of airway collapse that may require varying pressures different from the one the patient is using, as well as anatomical factors that may be corrected to help with compliance.